The Road Taken: An Archaeologist’s Journey to the Land of the Bible - Gitin, Seymour (Royal Inscriptions of the Neo-Assyrian Period, 2021)
Frontmatter -- Contents -- Preface -- Acknowledgments -- 1. Early Years, 1936–1956 -- 2. Rabbinic Studies in Cincinnati and Israel, 1956–1962 -- 3. Into the Real World: The Military and Civilian Rabbinate, 1962–1967 -- 4. A New Direction, 1967–1970: The Road to Archaeological Studies -- 5. Doctoral Studies and Excavations in Israel, 1970–1979 -- 6. Albright Institute: A New Beginning and a Vision for the Future, 1979– -- 7. Albright Institute: First Decade, 1980–1989 -- 8. Albright Institute: Second Decade, 1990–1999 -- 9. Albright Institute: Third Decade, 2000–2009 -- 10. Albright Institute: Fourth Decade, 2010–2014 -- Epilogue -- Appendixes -- Notes -- References -- Index